Challenges and Perspectives for Integrating Quinoa into the Agri-Food System - Irfan Afzal; Muhammad Zia Ul Haq; Shahbaz Ahmed; Abdelaziz Hirich; Didier Bazile (Plants, 2023)
Quinoa is a highly nutritious and abiotic stress-tolerant crop that can be used to ensure food security for the rapidly growing world population under changing climate conditions. Various experiments, based on morphology, phenology, physiology, and yield-related attributes, are being conducted across the globe to check its adoptability under stressful environmental conditions. High weed infestation, early stand establishment, photoperiod sensitivity, loss of seed viability after harvest, and heat stress during its reproductive stage are major constraints to its cultivation. The presence of saponin on its outer surface is also a significant restriction to its local consumption. Scientists are using modern breeding programs, such as participatory approaches, to understand and define breeding goals to promote quinoa adaptation under marginalized conditions. Despite its rich nutritional value, there is still a need to create awareness among people and industries about its nutritional profile and potential for revenue generation. In the future, the breeding of the sweet and larger-grain quinoa varietals will be an option for avoiding the cleaning of saponins, but with the risk of having more pests in the field. There is also a need to focus on mechanized farming systems for the cultivation, harvesting, and processing of quinoa to facilitate and expand its cultivation and consumption across the globe, considering its high genetic diversity.